Plastic waste and its method of recycling - Marsi, Noraini; Huzaisham, Nur Athirah; Ithnain, Zuraidah; Main, Nor Mazlana; Roslan, Mohd Nazrul; Shaari, Muhammad Farid; Kamarudin, Khairu (Penerbit UTHM, 2020)
Plastics waste is one of the major problems the world is currently facing due to the increase in plastic production and their demands in emerging economies. One of the concerns of plastic is unsystematic disposal problem that leads to an increase in plastic waste accumulation which can last forever in the environment and causing sever pollution..